Genetic health professionals' experiences returning results from diagnostic genomic sequencing to patients. Issue 5 (19th December 2019) - Vears, Danya F.; Sénécal, Karine; Borry, Pascal
Abstract: Despite widespread use of genomic sequencing (GS) in clinical care, there has been little exploration of actual experiences of genetic health professionals (GHPs) using GS in clinical practice worldwide. To address this, semi‐structured interviews were conducted with 31 clinical geneticists and genetic counselors across Europe, Australia, and Canada to explore their experiences with returning results from GS to patients. GHPs remarked that patients' reactions to receiving causative results vary; some patients are relieved or appreciative at identification of a genetic cause, while others express frustration that finding an answer does not lead to a treatment. GHPs discussed the importance of managing expectations in pre‐test counseling to minimize disappointment. Although some patients experience mild distress, they generally cope well receiving unsolicited findings and appreciate being informed of their increased risk. While many GHPs felt patients understand what a variant of uncertain significance (VUS) means, a proportion found VUS quite difficult to convey and had concerns for patients' level of understanding. A proportion mentioned concerns regarding potential negative repercussions of non‐genetic clinicians misinterpreting the significance of VUS. These results provide important insights into the challenges GHPs can experience returning GS results to patients, highlighting a need for additional training for GHPs and non‐genetic clinicians.